EP932 Impact of FDG-PET/CT in initial staging of primary advanced ovarian cancer. (1st November 2019) - Morillas, B; Caresia, AP; Ribot, L; Garcia, Y; Codina, C; Costa, I; Corona, M; Antoni, J; Canet, Y
Abstract : Introduction/Background: Primary surgical cytoreduction followed by systemic chemotherapy is the preferred initial management for women with stage III or IV ovarian cancer. Patients considered unresectable due to the location and volume of disease involvement or deemed unoperable because of medical comorbidities at the time of diagnosis may be considered for neoadjuvant chemotherapy. The aim of the study is to compare the pre-surgical staging findings in patients with locally advanced ovarian neoplasia by CT and 18F-FDG-PET/CT in our institution. Methodology: We included 34 locally advanced ovarian cancer patients (mean age 62.6, range 40–88) (IOTA M ultrasound findings) at initial staging. CT and PET/CT were performed and findings are compared. We analyzed changes in FIGO staging. Distant metastasis were pathologically confirmed when feasible. Results: PET/CT revealed distant metastasis in 20/28 patients (60.7%), mainly in supradiaphragmatic lymph nodes (18/20 patients), associated with addicional metastasis in pleura, inguinal adenopathies, liver or bone. FIGO stage was modified in 35.3% (12/34 patients) according to PET/CT. All of them were upstaged because of additional peritoneal or distant metastases. In the remaining 22/34 patients (64.7%) CT and PET/CT results were concordant and no change in clinical management was made. Conclusion: Initial staging of advanced ovarian cancer can be improved using FDG-PET/CT instead of diagnostic CT, mainly due to the detection of unsuspected distant metastasis. Supradiaphragmatic lymph nodes were the most frequent site of metastasis. FDG-PET/CT could make a decisive contribution to final management at least in a third of patients. Disclosure: Nothing to disclose.